A recombinant human collagen hydrogel for the treatment of partial-thickness burns: A prospective, self-controlled clinical study. Issue 3 (May 2021) - Ben, Chi; Liu, Xiaobin; Shen, Tuo; Song, Yanling; Li, Haihang; Pan, Bohan; Hou, Wenjia; Liu, Tong; Luo, Pengfei; Ma, Bing; Sun, Yu; Xiao, Shichu; et al.
Highlights: The research group constructed a hydrogel dressing based on recombinant human collagen, a new type of biological material. As gold treatments for partial deep skin burns, Xenogeneic skin was used as control group in this clinical study. There was no significant statistically difference between two groups in wound healing days (21 patients with 42 wounds). The recombinant human collagen gel is expected to be an optional substitute for the homologous/heterologous skin. Abstract: Introduction: Allogeneic and xenogeneic skin are recognized as the best coverings for skin burn wounds, but currently face a supply shortage. To solve this problem, our research group developed a standardized manufactured hydrogel dressing based on a new type of highly bioactive recombinant human collagen. Study design: Prospective self-controlled trial. Objective: To evaluate the efficacy and safety of recombinant human collagen hydrogel in the treatment of partial burn wounds to the skin compared to those of xenogeneic skin. Methods: This study included twenty-one patients admitted to Shanghai Changhai Hospital within 48 h after receiving partial-thickness skin burns. The wounds were symmetrically separated along the axis and treated with recombinant human collagen hydrogel (RHCH) or a human- CTLA4-Ig gene-transferred pig skin xenotransplant. The condition of the wound surfaces was recorded on days 0 (of enrollment), 5, 10, 15, and 20, and bacterial drug sensitivity testing, hematuria examination, and electrocardiographic tests were conducted on days 0, 10, 20, or on the day of wound healing. Results: There were no statistically significant differences in wound healing time between the two groups. The median number of days to healing was 11.00 ± 0.56 for xenogeneic skin vs. 11.00 ± 1.72 for RHCH. Conclusion: During the observation period, the therapeutic effect of the RHCH developed by our group on partial-thickness burn wounds was not significantly different from that of gene-transferred xenogeneic skin. Thus, our designed RHCH shows potential for clinical use to treat burn wounds on the skin.